ON INFORMATION SUPPORT FOR WASTE INVENTORY IN ROSTOV REGION - Elena Alexandrovna Kontsurova; Svetlana Nikolayevna Kholodova (Advanced Engineering Research, 2012)
The introduction and working prospects of the waste inventory in the Rostov Region are considered. Objectives, tasks, and advantages of the regional waste inventory are presented. The comparative analysis of the current environmental protection system in Rostov Region and the environmental protection system in the Czech Republic is done. The information support pros and cons in the area of waste are identified. New techniques and solutions to the assigned problem are offered.